(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3BNQgG (B:s
(3hJTQH GdKhH GdYQb (B: (3Gi fTag hGdJTYH (B: (3GdJaQb hGdJWdH (B: (3GdWdH eQg HYO eQg hjbGd (B: (3JYbH Ydjg ef GdeYJbHg , hJYLH efg (B:(3Gi YLH hJYQH Gi UGQ GYQGHjG JYRH ReGfG ,Gi GbGe Ydi GdYRhHg s
(3fSNI JJab ChdgG eY Chd fSNI edi edc (B- (3WgQGf (B345 (3HGNJdGa ai HYV GdCdaGXs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs